Investigative journalism in China : eight cases in Chinese watchdog journalism - Bandurski, David; Hala, Martin, 1961- (Hong Kong University Press, 2010)
"Despite persistent pressure from state censors and other tools of political control, investigative journalism has flourished in China over the last decade. This volume offers a comprehensive, first-hand look at investigative journalism in China, including insider accounts from reporters behind some of China's top stories in recent years. While many outsiders hold on to the stereotype of Chinese journalists as docile, subservient Party hacks, a number of brave Chinese reporters have exposed corruption and official misconduct with striking ingenuity and often at considerable personal sacrifice. Subjects have included officials pilfering state funds, directors of public charities pocketing private donations, businesses fleecing unsuspecting consumers -- even the misdeeds of journalists themselves. These case studies address critical issues of commercialization of the media, the development of ethical journalism practices, the rising spectre of 'news blackmail, ' negotiating China's mystifying bureaucracy, the dangers of libel suits, and how political pressures impact different stories. During fellowships at the Journalism & Media Studies Centre (JMSC) of the University of Hong Kong, these narratives and other background materials were fact-checked and edited by JMSC staff to address critical issues related to the media transitions currently under way in the PRC. This engaging narrative gives readers a vivid sense of how journalism is practiced in China"--Jacket